Streptomyces chrysomallus FKBP-33 is a novel immunophilin consisting of two FK506 binding domains; its gene is transcriptionally coupled to the FKBP-12 gene. - Pahl, A (1994)
The nucleotide sequence of the region 5' to the fkbA gene, encoding the Streptomyces chrysomallus FK506 binding protein (FKBP-12), revealed an open reading frame (fkbB) encoding a protein of 312 amino acids, with an M(r) of approximately 33,000. FkbB and fkbA appear to be co-transcribed under the control of a promoter upstream of fkbB. The presumptive protein encoded by fkbB would be an FKBP (designated FKBP-33) consisting of two FK506 binding domains with 43 and 32% sequence identity to FKBP-12 and a signal peptide sequence characteristic of bacterial membrane lipoproteins. The portion of the gene comprising the two FKBP domains, as well as each individual domain, were expressed as fusion proteins in Escherichia coli and purified. Each expressed domain, as well as FKBP-33 itself, possesses peptidyl-prolyl cis-trans isomerase activity, though with much lower specific activities than FKBP-12. FKBP-33 is located in the cell membrane of S.chrysomallus and of other streptomycetes, as predicted from the presence of the signal peptide sequence. Pulse-chase experiments with radioactive palmitate in whole cells revealed significant labelling of FKBP-33, which probably carries palmitate at its N-terminus and an additional diacylglycerol residue attached to the N-terminal cysteine in thioether linkage. The two domains of FKBP-33 showed considerable homology with numerous eukaryotic and prokaryotic FKB domains. Calculations of phylogenetic relationships indicate with high probability that the two domains of the protein have arisen by a double gene duplication of fkbA lying in tandem to fkbB.